Production and productivity of rice and sugar cane crops in Costa Rica from 1980 to 2010 - Morales Abarca, Luis Fernando (2018)
The objective of the research was to determine the data of production and productivity of crops of rice and sugar cane in Costa Rica, in order to analyze its behavior between 1980 and 2010. The official data compiled by the National Corporation of Rice Producers (CONARROZ), the Agricultural and Industrial League of the Sugar Cane (LAICA) and of the United Nations Organization for Food and Agriculture (FAO) were used. The main conclusion was that the rice showed a behavior of unstable in terms of production and productivity, while the cultivation of sugar cane introduced a relatively stable behavior with respect to production and productivity, between 1980 and 2010, with significant growth in productivity between 1990 and 2007.